Jawabanmu

2014-07-11T06:15:57+07:00
Tan²x + 1 = a²
tan² x = a² -1
tan x = √(a² - 1) =  \frac{depan}{samping}
                           *depan = √(a² - 1)
                            samping = 1          [buat segitiganya]
                         *miring² = depan² + samping²
                          miring  =  \sqrt{(a^2-1)^2 + 1^2}
                          miring  =  \sqrt{(a^2-1) + 1} = √a² = a

sin x =  \frac{depan}{miring} =  \frac{ \sqrt{a^2-1} }{a}
sin²x =  (\frac{ \sqrt{a^2-1} }{a})^2
         =  \frac{ a^2-1 }{a^2}